Polyphenols, Olive oil and Colonrectal cancer: the effect of Mediterranean Diet in the prevention - Mattioli, Anna Vittoria; Serra, Francesco; Spatafora, Francesco; Toni, Silvia; Farinetti, Alberto; Gelmini, Roberta (Acta Biomedica Atenei Parmensis, 2022)
In recent years, scientific research has shown that the incidence of various diseases, including some cancers, is relatively low in the Mediterranean Countries compared to that of other European countries or North America. This support the hypothesis that the Mediterranean diet, rich in bioactive food components, including methyl group donors, polyphenols, and fatty acids has efficacy in terms of prevention.Few studies evaluated the efficacy of Med Diet on colon cancer however they all support the beneficial effects of this Diet in preventing cancer.